Ugandan Music in the Marketing Era: The Branded Arena. David G. Pier. 2015. New York: Palgrave Macmillan. 8 images, 5 figures, 2 tables, index, 203pp. - Moon, Jocelyn (International Library of African Music, 2016)
pages: 221-223
Keywords: Music; African Music; Uganda; Marketing Era